Lithium ion battery composite diaphragm, preparation method thereof and lithium ion battery

By embedding lithium powder on the composite separator of the lithium-ion battery, the problem of lithium-ion battery loss during the first charge and discharge and cycle of the lithium-ion battery is solved, and the battery's high efficiency and long life are achieved.

CN119447701APending Publication Date: 2025-02-14CHINA ENERGY INVESTMENT CORP LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310955787.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-01
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

During the first charging and discharging process, lithium ions are consumed due to the formation of the SEI film, resulting in a decrease in the battery capacity and low charge and discharge efficiency for the first time. During the cycling process, the SEI film rupture leads to loss of lithium ions, affecting the battery circulation performance.

Method used

Lithium powder is embedded on the composite separator of the lithium-ion battery. By applying the adhesive layer on the surface of the separator and dispersing the lithium powder to deposit, cooling and standing to ensure that the lithium powder penetrates into the internal layer, thereby replenishing the lost during charging and discharging. lithium.

Benefits of technology

The first charging and discharging efficiency and cycle life of lithium-ion batteries were improved. The experimental results showed that the first efficiency was increased to 93.1%, and the cycle life was 97% at 370 weeks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004372400330000011
    Figure HDA0004372400330000011
  • Figure HDA0004372400330000012
    Figure HDA0004372400330000012
  • Figure HDA0004372400330000021
    Figure HDA0004372400330000021
Patent Text Reader

Abstract

The invention discloses a lithium ion battery composite membrane, a preparation method thereof and a lithium ion battery. The composite membrane comprises a base membrane, an adhesive layer on the surface of the base membrane and lithium powder attached to the surface of the adhesive layer. The preparation method is simple, and the metal lithium powder is dispersed and distributed on the surface of the adhesive layer, so that not only is the adhesion of the pole piece and the diaphragm stronger, but also the lithium powder on the diaphragm can be embedded into the pole piece in the charging and discharging processes of the battery so as to supplement lithium lost in the first charging process, so that the lithium ion battery is more stable in charging and discharging, and the service life of the battery is prolonged. The first efficiency and the cycle life of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a lithium-ion battery composite diaphragm and a preparation method thereof, and a lithium-ion battery. Background Art

[0002] As a new energy source, lithium-ion batteries are favored by people for their advantages such as high specific capacity, high operating voltage, long service life, and no memory effect. With the progress of society, the requirements for the energy density of lithium-ion batteries are getting higher and higher. Usually, the negative electrode material of lithium-ion batteries will consume some lithium ions during the first charge and discharge process to form a solid electrolyte interface film covering the surface of the negative electrode material of the electrode, referred to as SEI film. The formation of SEI film consumes some lithium, which will cause the loss of lithium in the positive electrode material, thereby reducing the battery capacity and causing the first charge and discharge efficiency of the battery to be low. In addition, during the cycle of lithium-ion batteries, the SEI film will break due to the volume effect of the negative electrode material during the charge and discharge process. Therefore, during the cycle process, lithium-ion batteries will still consume additional lithium ions to repair the broken SEI film. There will be irreversible lithium in the positive and negative electrodes to varying degrees, resulting in capacity loss, which will cause serious attenuation of the battery's cycle performance. In order to improve the first charge and discharge efficiency of lithium-ion batteries and reduce the consumption of lithium by the formation of SEI film, the technology of lithium supplementation for lithium-ion batteries needs to be developed urgently.

[0003] At present, there are two main lithium insertion methods adopted by lithium-ion electrochemical systems. One is to add lithium compounds to the positive electrode. During the first charge and discharge, the excess lithium in the positive electrode will enter the negative electrode to supplement the lithium lost by the SEI film. Another method is to embed lithium compounds in the negative electrode material. During the first charge, the lithium embedded in the negative electrode can directly supplement the lithium during the charge and discharge process. For example, the related art discloses a method for preparing a lithium-supplementing composite diaphragm, in which a glue layer is coated on the positive electrode side of the base film, and a lithium-supplementing slurry rich in inorganic lithium salts is coated on the negative electrode side. The lithium source is various conventional inorganic lithium salts, such as lithium carbonate, lithium hydroxide, lithium chloride, etc. However, the oxidation potential of these lithium salts is usually higher than the decomposition potential of the electrolyte, and active lithium ions cannot be released without the use of special catalysts. Summary of the invention

[0004] In view of this, the main purpose of the present application is to provide a lithium-ion battery composite diaphragm and a preparation method thereof, and a lithium-ion battery, in which lithium powder is embedded in the diaphragm, the process is simple, and the initial efficiency and cycle life of the battery are improved.

[0005] To achieve the above-mentioned purpose of the invention, the first aspect of the present application provides a lithium-ion battery composite separator, comprising: a base film, a glue layer on the surface of the base film, and lithium powder attached to the surface of the glue layer.

[0006] Furthermore, the adhesive layer is PVDF adhesive or PTFE adhesive.

[0007] Furthermore, the base film is selected from a polyethylene film, a polypropylene film or a polypropylene / polyethylene / polypropylene composite film, and the thickness of the base film is 5 micrometers to 25 micrometers.

[0008] Furthermore, the lithium powder includes lithium powder or lithium alloy powder, and the lithium alloy is selected from an alloy consisting of lithium and at least one metal selected from Si, Mg, Al, Sn, Be, and Ti.

[0009] The second aspect of the present invention provides a method for preparing a lithium ion battery composite diaphragm, comprising the following steps:

[0010] Providing vaporized lithium powder;

[0011] Applying a glue layer on the surface of the diaphragm, and allowing the vaporized lithium powder to be dispersed and deposited on the surface of the glue layer, cooling and standing, to obtain a lithium-ion battery composite diaphragm;

[0012] Furthermore, the lithium powder is gasified at a high temperature, wherein the gasification temperature is 1100-1250°C.

[0013] Furthermore, the temperature during the deposition of the lithium powder is ≤85°C, preferably 75-85°C.

[0014] Furthermore, the deposition is performed by using a magnetic field sputtering method, so that the lithium powder is evenly scattered on the surface of the glue layer under the action of the magnetic field.

[0015] Furthermore, the pressure during the deposition of the lithium powder is 0.1Pa-0.6Pa.

[0016] Furthermore, according to the gram capacity of the metallic lithium powder of 1500 mAh / g, the deposited lithium powder is 62.5 mg-65 mg, and the particle size of the lithium powder is preferably 150-200 nm.

[0017] Furthermore, the cooling and standing conditions include: standing at 70-80°C for 0.5-3 hours, preferably standing at 80°C for 2.5 hours.

[0018] The third aspect of the present invention provides an application of a lithium-ion battery composite diaphragm as a diaphragm on the negative electrode plate side.

[0019] A fourth aspect of the present invention provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet and the above-mentioned composite separator.

[0020] Compared with the prior art, this application has the following advantages:

[0021] The present application provides vaporized lithium powder; a glue layer is coated on the surface of the diaphragm, and the vaporized lithium powder is deposited on the surface of the glue layer to achieve the dispersed distribution of the lithium powder on the surface of the glue layer. The lithium powder can penetrate into the glue layer after cooling and standing for a period of time to ensure the embedding of metallic lithium. Therefore, the present invention disperses metallic lithium powder on the surface of the glue layer. This method not only makes the adhesion between the pole piece (such as the negative electrode) and the diaphragm stronger, but also during the charging and discharging process of the battery, the lithium powder on the diaphragm will be embedded in the negative electrode during the charging and discharging process to supplement the lithium lost during the first charging process, thereby improving the first efficiency and cycle life of the battery. The experimental results show that the first efficiency of the battery is increased from 88.2% to 93.1%. In addition, the capacity retention rate of the battery cycle life is 97% at 370 weeks.

[0022] Other features and advantages of the present application will be described in detail through the following specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The electron microscope image of the polyethylene film is shown.

[0024] Figure 2 The electron microscope image of the base film coated with PVDF adhesive layer is shown.

[0025] Figure 3 The electron microscope image of the composite membrane after lithium insertion is shown.

[0026] Figure 4 The first charge and discharge curves of the lithium-ion battery prepared using the diaphragm of Comparative Example 1 are shown.

[0027] Figure 5 The comparison of the cycle stability of the 1.5Ah soft-pack battery prepared with the composite membrane of Example 1 (shown by the upper line) and the full battery prepared with the conventional membrane of Comparative Example 1 (shown by the lower line) is shown.

[0028] Figure 6 The first charge and discharge curves of the lithium-ion battery prepared using the composite separator of Example 1 are shown.

[0029] Figure 7 The first charge and discharge curves of the lithium-ion battery prepared using the composite membrane of Example 2 are shown.

[0030] Figure 8 The comparison of the cycle capabilities of the lithium-ion batteries prepared in different Examples 1-3 is illustrated. DETAILED DESCRIPTION

[0031] The following will clearly and completely describe the concept of the present application and the technical effects produced in combination with the embodiments, so as to fully understand the purpose, features and effects of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of them. Based on the embodiments of the present application, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present application.

[0032] In the description of the embodiments of the present application, if orientation descriptions are involved, the orientations or positional relationships indicated by "up", "down", "front", "back", "left", "right", etc. are based on the orientations or positional relationships shown in the accompanying drawings. They are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or device referred to must have a specific orientation, be constructed and operated in a specific orientation. Therefore, they cannot be understood as limitations on the present application.

[0033] In the description of the embodiments of the present application, if a feature is referred to as being “set,” “fixed,” “connected,” or “installed” on another feature, it may be directly set, fixed, or connected to another feature, or it may be indirectly set, fixed, connected, or installed on another feature. In the description of the embodiments of the present application, if “several” is involved, it means more than one; if “multiple” is involved, it means more than two; if “greater than,” “less than,” or “exceeds” is involved, it should be understood as not including the number itself; if “above,” “below,” or “within” is involved, it should be understood as including the number itself. If “first” or “second” is involved, it should be understood as being used to distinguish technical features, and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.

[0034] A first aspect of the present invention provides a lithium-ion battery composite separator, comprising: a base film, a glue layer on the surface of the base film, and lithium powder attached to the surface of the glue layer.

[0035] Preferably, the adhesive layer can be made of a colloid with bonding effect, such as PVDF glue or PTFE glue.

[0036] Preferably, the base film is selected from a polyethylene film, a polypropylene film or a polypropylene / polyethylene / polypropylene composite film, and the thickness of the base film is 5 microns to 25 microns.

[0037] Preferably, the lithium powder includes lithium powder or lithium alloy powder, and the lithium alloy is selected from an alloy consisting of lithium and at least one metal selected from Si, Mg, Al, Sn, Be, and Ti.

[0038] In the present invention, the lithium powder is passivated lithium powder. Depending on the test conditions, active lithium powder can also be used. For example, when the dew point moisture in the operating space reaches -40 degrees (i.e., the moisture content is 0.1757 g / m 3 ), active lithium powder can be used to ensure effective control of moisture.

[0039] The present invention also provides a method for preparing a lithium ion battery composite diaphragm, comprising the following steps:

[0040] Providing vaporized lithium powder;

[0041] Applying a glue layer on the surface of the diaphragm, and allowing the vaporized lithium powder to be dispersed and deposited on the surface of the glue layer, cooling and standing, to obtain a lithium-ion battery composite diaphragm;

[0042] Preferably, the lithium powder is gasified at a high temperature, and the gasification temperature is 1100-1250° C. After gasification, the parameters may be kept stable for a period of time, illustratively 20-40 minutes, without changing them.

[0043] Preferably, the temperature during the deposition of the lithium powder is ≤85°C, preferably 75-85°C.

[0044] Preferably, the deposition is performed by magnetic field sputtering, so that the lithium powder is evenly scattered on the surface of the adhesive layer under the action of the magnetic field. Preferably, the pressure during the deposition of the lithium powder is 0.1Pa-0.6Pa.

[0045] Preferably, based on the gram capacity of metal element lithium powder of 1500mAh / g, the deposited lithium powder is 62.5mg-65mg; in some examples, the required amount of lithium powder = gram capacity of lithium metal * mass of metal lithium / negative electrode surface density, for example: if the result of the above formula is 0.2, the lithium supplementation is about 20%.

[0046] Preferably, the particle size of the lithium powder is 150-200 nm. Lithium powder with a small particle size is difficult to prepare directly, and the particle size of lithium powder at the micron level is too large, which causes the flow rate of lithium ions to be weakened, thereby affecting the rate and internal resistance.

[0047] Preferably, the cooling and standing conditions include: standing at 70-80°C for 0.5-3 hours, preferably standing at 80°C for 2.5 hours.

[0048] In this article, the coating of the adhesive layer on the surface of the diaphragm refers to the existing related technology.

[0049] The present invention also provides a preparation system for a lithium-ion battery composite diaphragm, comprising a lithium powder treatment area and a feeding area, wherein the lithium powder treatment area is used to gasify lithium powder under high temperature, and the diaphragm coated with a rubber layer enters the lithium powder treatment area from the feeding area; the interior of the lithium powder treatment area is cooled, and the gasified lithium is dispersed and deposited on the surface of the rubber layer of the diaphragm under pressure, and then the internal temperature of the lithium powder treatment area is maintained below 85°C, and the lithium powder is allowed to stand for a period of time to penetrate into the rubber layer of the diaphragm, thereby obtaining a composite diaphragm embedded with metallic lithium.

[0050] Preferably, the deposition rate in the system treatment area is changed to change the uniformity of the lithium powder deposition on the surface of the glue layer.

[0051] The present invention also provides an application of the composite diaphragm as a diaphragm on the negative electrode plate side.

[0052] The present invention also provides a lithium-ion battery, including a positive electrode sheet, a negative electrode sheet and the composite separator. The manufacturing process of the lithium-ion battery refers to the existing related technology, for example, including the following steps:

[0053] The raw materials of the positive electrode or the negative electrode are respectively homogenized, coated, and pressed to prepare a positive electrode sheet or a negative electrode sheet;

[0054] Assembling the composite diaphragm prepared by the present invention, the positive electrode sheet, and the negative electrode sheet into a soft-pack battery in the form of a stack;

[0055] The preparation of soft-pack batteries is completed through the steps of welding, edge sealing, film pasting, drying, liquid injection, high temperature pressurization, formation, aging and capacity determination.

[0056] It is worth noting that when the composite diaphragm of the present invention is used to prepare a lithium-ion battery, the temperature during high-temperature pressing does not exceed 75°C, and the hot pressing time is preferably 4-6 hours. If the hot pressing time is too long, the composition of the electrolyte in the battery may change, and if the hot pressing time is too short, the metal lithium powder therein will not fully penetrate into the battery.

[0057] The composite diaphragm of the present invention is suitable for iron lithium-graphite system, high nickel ternary-graphite system, lithium cobalt oxide-graphite system, NCA-graphite system, lithium titanate negative electrode system and the like.

[0058] The following examples are used to illustrate the composite membrane of the present application and its preparation and application.

[0059] Main raw materials description:

[0060] The purity of lithium powder is battery-grade lithium powder, and the manufacturer is Wuxi Xinneng Lithium Industry;

[0061] Diaphragm base film: 16 micron base film (polyethylene diaphragm, referred to as PE) produced by Enjie Company;

[0062] PVDF rubber powder: produced by Solvay, model 5130.

[0063] Example 1

[0064] Using the TH-SC6-A00 lithium embedding equipment customized by Xiji, lithium powder is vaporized in the lithium powder treatment area by high temperature. The vaporization temperature is 1200℃ and kept stable for 30 minutes. Then the polyethylene film coated with PVDF glue powder is placed from the feed area to the treatment area. The lithium vaporized in the treatment area will be deposited on the PVDF glue layer by magnetic field sputtering under the pressure of 0.4Pa. Then, the lithium powder can be evenly coated on the surface of the diaphragm glue layer through the bonding effect of PVDF glue powder and lowering the temperature to 80℃. After that, it is allowed to stand at 80℃ for 2.5 hours to allow the lithium powder to penetrate into the PVDF glue layer to ensure the embedding of metallic lithium and obtain a lithium-ion battery composite diaphragm.

[0065] In this embodiment, the mass of embedded lithium powder is 65 mg. Figure 1 The electron microscope image of the polyethylene film is shown. Figure 2 The electron microscope image of the base film coated with PVDF adhesive layer is shown. Figure 3 The electron microscope image of the composite diaphragm after lithium insertion is shown. It can be seen from the image that after the deposition by the sputtering process, all the lithium powder is sputtered onto the surface of the diaphragm, and the surface is dense.

[0066] The particle size of the lithium powder used in this embodiment is 150-200 nm, and the particle size is uniform and consistent.

[0067] The composite diaphragm of this embodiment is used as the diaphragm on the negative electrode plate side and is used to prepare a lithium-ion battery. The basic process parameters of the battery are shown in Table 1 below:

[0068] Table 1

[0069] Design capacity 1.5Ah Negative / positive 1.04 Positive electrode activity ratio 95% Negative electrode activity ratio 94.50% Cathode Materials <![CDATA[Li(Ni 0.33 What 0.3 3Mn 0.33 )O2]]> Anode Materials Coal-based anode Positive electrode surface density <![CDATA[30.4mg / cm 2 ]]> Negative electrode surface density <![CDATA[13.4mg / cm 2 ]]> Positive electrode width 84mm Negative electrode width 88mm Cathode compaction <![CDATA[3.2g / cm 3 ]]> Negative electrode compaction <![CDATA[1.55g / cm 3 ]]> Diaphragm width 96mm Number of lamination layers 7 positive electrode 8 negative electrode Diaphragm status Single-sided PVDF adhesive Lithium coating amount of diaphragm 65mg Injection volume 9.5g Hot pressing temperature 75℃ 6 hours

[0070] Example 2

[0071] The difference from Example 1 is that the mass of the lithium powder is 62.5 mg, the particle size of the lithium powder is adjusted to 500 nm in this example, and the initial efficiency of the battery is reduced to 90%.

[0072] Example 3

[0073] The difference from Example 1 is that the mass of lithium powder is 50 mg and the particle size is 200 nm. In this example, the lithium powder content is reduced to 50 mg, and the cycle capacity of the battery is significantly reduced, which is reduced to 80% after 500 cycles.

[0074] Comparative Example 1

[0075] The difference from Example 1 is that conventional polyethylene separator NT1602 is used and lithium powder is not embedded.

[0076] Figure 4 The first charge and discharge curves of the conventional separator lithium-ion full battery in comparative example 1 are shown. The first efficiency reached 88.3%. Figure 5 The cycle stability comparison of the 1.5Ah soft pack battery prepared with the composite diaphragm in Example 1 and the full battery prepared with the conventional diaphragm in Comparative Example 1 is shown. The capacity retention rate is 97.2% after 350 cycles at a rate of 1C. The cycle life of the lithium-embedded battery is higher than that of the conventional battery. Figure 6 The first charge and discharge curves of the negative electrode sheet of the lithium-ion battery including the composite separator of Example 1 are shown. Figure 6 It can be seen that after pre-embedded lithium, the initial efficiency of the full battery reached 93.1%. Figure 7 The first charge and discharge curves of the lithium-ion battery prepared using the composite membrane of Example 2 are shown. Figure 8 The comparative cycle data of the lithium-ion batteries prepared in Examples 1-3 show that when the size and particles of the metallic lithium are lower than the preferred values, the cycle capacity of the entire battery will decrease.

[0077] Obviously, the above embodiments of the present application are merely examples for clearly illustrating the present application, and are not intended to limit the implementation methods of the present application. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all implementation methods here. All obvious changes or modifications derived from the technical solutions of the present application are within the spirit scope covered by the present application.

Claims

1. A lithium-ion battery composite diaphragm, characterized in that: include: The base film, the adhesive layer on the surface of the base film and the lithium powder attached to the surface of the adhesive layer.

2. The composite diaphragm according to claim 1, characterized in that: The adhesive layer is PVDF adhesive or PTFE adhesive.

3. The composite diaphragm according to claim 1, characterized in that: The base film is selected from a polyethylene film, a polypropylene film or a polypropylene / polyethylene / polypropylene composite film; the thickness of the base film is preferably 5 microns to 25 microns.

4. The composite diaphragm according to claim 1, characterized in that: The lithium powder includes lithium powder or lithium alloy powder, and the lithium alloy is selected from an alloy consisting of lithium and at least one metal selected from Si, Mg, Al, Sn, Be, and Ti.

5. A method for preparing a lithium ion battery composite diaphragm, characterized in that: The steps include: Providing vaporized lithium powder; A glue layer is coated on the surface of the diaphragm, and vaporized lithium powder is dispersed and deposited on the surface of the glue layer, and the temperature is reduced and allowed to stand to obtain a lithium-ion battery composite diaphragm.

6. The method for preparing the composite diaphragm according to claim 5, characterized in that: The lithium powder is gasified at a high temperature, wherein the gasification temperature is 1100-1250°C.

7. The method for preparing the composite diaphragm according to claim 5, characterized in that: The temperature of the lithium powder during deposition is ≤85°C, preferably 75-85°C; and / or, The deposition adopts a magnetic field sputtering method; and / or, Calculated based on the gram capacity of metallic lithium powder of 1500 mAh / g, the deposited lithium powder is 62.5 mg-65 mg, and the particle size of the lithium powder is preferably 150-200 nm.

8. The method for preparing the composite diaphragm according to claim 5, characterized in that: The cooling and standing conditions include: standing at 70-80° C. for 0.5-3 hours, preferably standing at 80° C. for 2.5 hours.

9. Use of the composite diaphragm according to any one of claims 1 to 4 or the composite diaphragm prepared by the method according to any one of claims 5 to 8 as a diaphragm on the negative electrode plate side.

10. A lithium-ion battery comprising a positive electrode sheet, a negative electrode sheet, and a composite diaphragm according to any one of claims 1 to 4 or a composite diaphragm prepared by the method according to any one of claims 5 to 8.